Plastik Sanatlar Alanında Seramik ve Cam Üzerine Yaklaşımlar 2-Akça - Tazeoğlu Filiz, Ferda; Tonza Helvacıkara, Fidan; Gülaçtı, Nurettin; Gümüş Akman, Nagihan; Kuyrukcu, Dilek; İba, Şeyma Müge and Uslu, Ali and Görgünay, Gamze and Tanrıverdi, Yaprak and Yılmazer, Yunis and Erdem, Bahadır Cem (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-